2008
DOI: 10.1021/jp077429y
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Sugar Radicals in RNA Model Systems and Oligomers via Excitation of Guanine Cation Radical

Abstract: In previous work, we have shown that photoexcitation of guanine cation radical (G*+) in frozen aqueous solutions of DNA and its model compounds at 143 K results in the formation of neutral sugar radicals with substantial yield. In this report, we present electron spin resonance (ESR) and theoretical (DFT) evidence regarding the formation of sugar radicals after photoexcitation of guanine cation radical (G*+) in frozen aqueous solutions of one-electron-oxidized RNA model compounds (nucleosides, nucleotides and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
99
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(121 citation statements)
references
References 43 publications
22
99
0
Order By: Relevance
“…As discussed in the introduction, it has been observed that sugar radical formation in dGuo 26 and in Guo 27 via photo-excitation of one-electron oxidized G depends on the protonation state of the one-electron oxidized guanine, and hence, on the pH of the solution. Substantial sugar radical formation (>80%) via photo-excitation of the cation radical (G• + ) but, at pH ≥9, only G(N1-H)• is present and only small amounts (ca.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed in the introduction, it has been observed that sugar radical formation in dGuo 26 and in Guo 27 via photo-excitation of one-electron oxidized G depends on the protonation state of the one-electron oxidized guanine, and hence, on the pH of the solution. Substantial sugar radical formation (>80%) via photo-excitation of the cation radical (G• + ) but, at pH ≥9, only G(N1-H)• is present and only small amounts (ca.…”
Section: Resultsmentioning
confidence: 99%
“…≤10%) sugar radicals are been found on photoexcitation. 26, 27 Production of sugar radical in the ss DNA and RNA oligomers have also been reported via photo-excitation of G• + . 8, 26, 27, 2931 Thus, arguing from the pH dependence in the formation of sugar radicals via photo-excitation of nucleosides discussed above, it is expected that the extent of photo-conversion to sugar radicals via photo-excitation of G(N1-H)•:C(+H + ) might be significantly larger that that via photo-excitation of G(N1-H)•:C with the greatest extent of sugar radical formation on photo-excitation of the cation radical G• + :C. This hypothesis is tested in this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Moreover there is experimental evidence proving that oxidative events in the deoxyribose moiety are directly related to DNA strand scissions. [36][37][38][39] There are four mechanisms proposed so far explaining lesions in the sugar unit: direct H abstraction by OH, 22,23,37,39 direct ionization of the sugar-phosphate backbone followed by deprotonation, 37 hole transfer from G + to the sugar ring by photo-induced excitation, 38,[41][42][43][44][45][46] and direct deprotonation of the sugar unit in ground-state 2dG + . 23,47 However the effects of the presence of base-pairing and phosphate, solvent, and physiological pH have not been simultaneously included in these investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Following our works on DNA and RNA-radicals, 79,141,142,148,152,[158][159][160][161][162][163][164][165][166] the anisotropic simulations of the experimentally recorded ESR spectra were carried out by employing the Bruker programs (WIN-EPR and SimFonia). The ESR parameters (e.g., hyperfine coupling constant (HFCC) values, linwidth, etc.)…”
Section: Analyses Of Epr Spectramentioning
confidence: 99%